Pathological examination of blended and co-electrospinning hybrid polycaprolactone/polyurethane nanofibers for soft tissue engineering applications. Issue 4 (June 2022) - Kazemzadeh, Gholamhosein; Jirofti, Nafiseh; Mohebbi-Kalhori, Davod; Sarhaddi, Farkhonde; Taheri, Reza
The main objective of soft tissue engineering (STE) is to improve the quality of life by replacing damaged tissues with synthetic scaffolds. Collagen is the key structural protein of the native extracellular matrix with nano-scale diameter. Accordingly, this study focused on the fabrication of the blended and co-electrospinning hybrid synthetic polycaprolactone/polyurethane (PCL/PU) nanofibers scaffolds and investigates their in-vivo biocompatibility for the development of their clinical applications in STE. The body reactions were evaluated by examination of the edema, foreign body granulomatous reaction, granulation tissue formation, inflammation, calcification, fibroblastic change, and necrosis as the most important healing effects in pathology examination. The blended and co-electrospinning PCL/PU structures were successfully carried out in the nano-scale range without any beads. According to the histopathological examination of PCL, the scant, mild and mild to moderate, and acute and chronic have been reported for edema, foreign body granulomatous reaction, and inflammation, respectively. Also, severe (for edema), moderate (for foreign body granulomatous reaction), and mild to moderate chronic (for inflammation) were observed for PU. In blended PCL/PU nanofibers, decreasing of the edema and foreign body granulomatous reaction and increasing of the granulation tissue formation and inflammation were observed with the increasing composite ratio of PCL from 25 to 75%. Also in the co-electrospinning hybrid PCL/PU nanofibers, increasing edema, granulation tissue formation, and inflammation were observed by increasing the composite ratio of PU from 25 to 75%. Present study suggested that blended hybrid PCL75/PU25 nanofibers are a promising candidate as synthetic nanofibers scaffolds for STE applications.